Synthesis and Characterization of Ca3Co4O9 Ceramic by using Sol-Gel Method - Sigit Dwi Yudanto; Septian Adi Chandra; Rahadian Roberto; Dedi Pria Utama; Lusiana -; Wafi Ahdilah; Virginia Octa Herlina (Balai Besar Keramik, 2021)
We report the synthesis of Ca3Co4O9 ceramics by the Sol-Gel method with citric acid as the chelating agent. Calcium nitrate and cobalt nitrate as precursors were weighed at an atomic ratio of Ca: Co = 3: 4. The process starts with gel preparation, followed by drying, calcination, and compaction process. The pellets were sintered at 820°C, 860°C, and 900°C for 6 hours in a furnace without flowing gas. The effect of sintering temperature on the formation of the Ca3Co4O9 phase was analyzed using an X-ray diffractometer. The Ca3Co4O9 phase has formed in samples sintered at 820°C with the Co3O4 phase as an impurity. Based on the calculation, the crystallite size decreases with increasing sintering temperature